Net Neutrality, Exclusivity Contracts and Internet Fragmentation - Kourandi,F; Kraemer,J; Valletti,T (Information Systems Research, 2015)
Net neutrality (NN) is believed to prevent the emergence of exclusive online content, which yields Internet fragmentation. We examine the relationship between NN regulation and Internet fragmentation in a game-theoretic model that considers the interplay between termination fees, exclusivity, and competition between two Internet service providers (ISPs) and between two content providers (CPs). An exclusivity arrangement between an ISP and a CP reduces the CP’s exposure to some end users, but it also reduces competition over ads among the CPs. Fragmentation arises in equilibrium when competition over ads among the CPs is very strong, the CPs’ revenues from advertisements are very low, the content of the CPs is highly complementary, or the termination fees are high. We find that the absence of fragmentation is always beneficial for consumers, because they can enjoy all available content. Policy interventions that prevent fragmentation are thus good for consumers. However, results for total welfare are more mixed. A zero-price rule on traffic termination is neither a sufficient nor a necessary policy instrument to prevent fragmentation. In fact, regulatory interventions may be ineffective or even detrimental to welfare and are only warranted under special circumstances.